Efficacy and Safety of 1-Hour Infusion of Recombinant Human Atrial Natriuretic Peptide in Patients With Acute Decompensated Heart Failure: A Phase III, Randomized, Double-Blind, Placebo-Controlled, Multicenter Trial. Issue 9 (March 2016) - Wang, Guogan; Wang, Pengbo; Li, Yishi; Liu, Wenxian; Bai, Shugong; Zhen, Yang; Li, Dongye; Yang, Ping; Chen, Yu; Hong, Lang; Sun, Jianhui; Chen, Junzhu; et al.
Abstract : Abstract: The aim of the study was to evaluate the efficacy and safety of 1-h infusion of recombinant human atrial natriuretic peptide (rhANP) in combination with standard therapy in patients with acute decompensated heart failure (ADHF). This was a phase III, randomized, double-blind, placebo-controlled, multicenter trial. Eligible patients with ADHF were randomized to receive a 1-h infusion of either rhANP or placebo at a ratio of 3:1 in combination with standard therapy. The primary endpoint was dyspnea improvement (a decrease of at least 2 grades of dyspnea severity at 12 h from baseline). Reduction in pulmonary capillary wedge pressure (PCWP) 1 h after infusion was the co-primary endpoint for catheterized patients. Overall, 477 patients were randomized: 358 (93 catheterized) patients received rhANP and 118 (28 catheterized) received placebo. The percentage of patients with dyspnea improvement at 12 h was higher, although not statistically significant, in the rhANP group than in the placebo group (32.0% vs 25.4%, odds ratio=1.382, 95% confidence interval [CI]: 0.863–2.212, P = 0.17). Reduction in PCWP at 1 h was significantly greater in patients treated with rhANP than in patients treated with placebo (−7.74 ± 5.95 vs −1.82 ± 4.47 mm Hg, P < 0.001). The frequencies of adverse events and renal impairment within 3 days of treatment were similar between the 2 groups. Mortality at 1 month was 3.1% in the rhANP group vs 2.5% in the placebo group (hazard ratio = 1.21, 95% CI: 0.34–4.26; P > 0.99). 1-h rhANP infusion appears to result in prompt, transient hemodynamic improvement with a small, nonsignificant, effect on dyspnea in ADHF patients receiving standard therapy. The safety of 1-h infusion of rhANP seems to be acceptable. (WHO International Clinical Trials Registry Platform [ICTRP] number, ChiCTR-IPR-14005719.)